2016
DOI: 10.1021/acs.organomet.6b00138
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Divalent Dialkyl Lanthanide-Catalyzed Cross-Dehydrocoupling of Silanes and Amines

Abstract: The rare-earth bis(alkyl) compound Sm{C-(SiHMe 2 ) 3 } 2 THF 2 (1b) is prepared by the reaction of samarium(II) iodide and 2 equiv of KC(SiHMe 2 ) 3 . This synthesis is similar to that of previously reported Yb{C-(SiHMe 2 ) 3 } 2 THF 2 (1a), and compounds 1a,b are isostructural. Reactions of 1b and 1 or 2 equiv of B(C 6 F 5 ) 3 afford SmC(SiHMe 2 ) 3 HB(C 6 F 5 ) 3 THF 2 (2b) or Sm{HB-(C 6 F 5 ) 3 } 2 THF 2 (3b), respectively, and 1,3-disilacyclobutane {Me 2 Si-C(SiHMe 2 ) 2 } 2 as a byproduct. Bands from 2300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 84 publications
2
32
0
Order By: Relevance
“…A recent study has shown that divalent rare earth alkyl complexes are effective catalysts for the cross-dehydrocoupling of silanes and amines to give silazanes. 47 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that divalent rare earth alkyl complexes are effective catalysts for the cross-dehydrocoupling of silanes and amines to give silazanes. 47 …”
Section: Resultsmentioning
confidence: 99%
“…Sadow and co‐workers synthesized samarium and ytterbium dialkyl complexes bearing NHC ligands, and good conversions were afforded by both compounds with primary and secondary silanes [53] . An experimental ternary rate law precluded the formation of M‐SiR 3 intermediates, and a coordinately unsaturated M‐NR 2 species was hypothesized to lead to Si−N bond formation.…”
Section: F‐block Catalystsmentioning
confidence: 99%
“…As a general rule, bulky hydrocarbyl ligands that lack β‐hydrogen atoms ([C(SiMe 3 ) 3 ], [C(SiMe 3 ) 2 (SiMe 2 CH=CH 2 )]) or contain Lewis base groups able to coordinate to the metal center ([C(SiMe 3 ) 2 (SiMe 2 OMe)], [Me 3 SiCH(C 6 H 4 )NMe 2 ], bis(phosphinimino)methanide) are used for this purpose. Sadow and co‐workers proposed an original way of stabilization of Ln II bis(alkyl) species via β‐SiH agostic interactions between Ln II and [C(SiHMe 2 ) 3 ] ligands . It is worth noting that mixed‐ligand Ln II alkyl species coordinated by supporting ligand are even more rare than homoleptic ones.…”
Section: Introductionmentioning
confidence: 99%